2022
DOI: 10.3389/fphar.2022.848263
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Inhibits Pulmonary Fibrosis by Regulating Cellular Senescence in Mice

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive disease, and its occurrence and development are mediated by cellular senescence. Drugs targeting senescent cells seem like a promising and efficacious strategy for IPF treatment. Previous studies have illustrated that pentoxifylline (PTX) may play a certain role in inhibiting pulmonary fibrosis and combating cellular senescence. In this study, we demonstrated that PTX administration inhibits pulmonary fibrosis development and cellular senescence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our previous research found that, PTX could influence the expression of fibrosis-related genes in the mouse model of pulmonary fibrosis. In addition, we also found that the expression of senescence-associated secretory phenotype (SASP) decreased in the PTX group (Lin et al, 2022). Therefore, we speculated that PTX might may also alleviate pulmonary fibrosis through anti-aging.…”
Section: Non-selective Phosphodiesterase Inhibitormentioning
confidence: 83%
“…Our previous research found that, PTX could influence the expression of fibrosis-related genes in the mouse model of pulmonary fibrosis. In addition, we also found that the expression of senescence-associated secretory phenotype (SASP) decreased in the PTX group (Lin et al, 2022). Therefore, we speculated that PTX might may also alleviate pulmonary fibrosis through anti-aging.…”
Section: Non-selective Phosphodiesterase Inhibitormentioning
confidence: 83%
“…Additionally, some plant extracts can also alleviate PF by targeting senescent cells. For example, pentoxifylline was found to regulate PAI-1 expression and inhibit lung fibroblast senescence, thereby exerting an anti-fibrotic effect [150,151]. These data suggest that cell senescence promotes the development of PF.…”
Section: Targeting Senescent Cellsmentioning
confidence: 88%
“…Pentoxifylline is a non-specific phosphodiesterase inhibitor that has been employed to manage intermittent claudication in peripheral vascular disease and alcoholic hepatitis [127,128]. Recently, the anti-inflammatory and antifibrotic attributes of pentoxifylline, which inhibits the Smad2/3/4 cascade and NF-κB, have been explored in diverse disease models including kidney fibrosis (Figure 2) [129][130][131][132][133][134][135].…”
Section: Pentoxifyllinementioning
confidence: 99%